Improving Students' Mathematic Concept Understanding Viewed from Self-Efficacy with RME-Based Krulik Rudnick Heuristic Learning Model - Komarudin, Komarudin; Yuberti, Yuberti; Pratiwi, Dona Dinda; Afandi, Muhamad; Wardani, Rani; Puspita, Laila (Indonesian Journal of Science and Mathematics Education, 2022)
A low understanding of mathematical concepts can affect a student's learning process. In overcoming this problem, teachers must pay attention to students’ self-efficacy. This quasi-experimental study aimed to determine the effect of the RME-based Krulik-Rudnick Heuristics learning model on understanding mathematical concepts regarding students' self-efficacy. The samples were obtained using the cluster random sampling technique. The data collection technique used was a test of description questions. Hypothesis testing was performed using two-way ANOVA. The research found that Fa was  F(0.05;1.45); therefore, H0A was rejected. Furthermore, Fb was lower than F(0.05;2;45), so H0B was accepted, and Fab was lower than F (0.05;2.45), so H0AB was accepted. It can be concluded that there was an effect of the learning model used on understanding mathematical concepts, there was no effect of self-efficacy (high, medium, and low) on mathematical concept understanding, and there was no interaction between learning models and self-efficacy (high, medium and low) on students' mathematical concepts understanding. It is recommended that further researchers apply RME-based Krulik-Rudnick Heuristics to other learning materials.